Effect of Myomectomy on Endometrial Glutathione Peroxidase 3 (GPx3) and Glycodelin mRNA Expression at the Time of the Implantation Window - Farimani Sanoee, Marzieh (Pasteur Institute of Iran, 2014)
Background: In fertile women, glycodelin and glutathione peroxidase 3 (GPx3) genes expression rises during the luteal phase, with a peak occurring during the implantation window. The expression of these genes decreases in women with myomas. To determine whether myomectomy would reverse glycodelin and GPx3 expression, we evaluated the transcript levels of these genes in the endometrium of patients before and after myomectomy. Methods: Expression of glycodelin and GPx3 genes were examined prospectively during the midluteal phase in the endometrium obtained from infertile women with myoma (n = 12) before and three months after myomectomy. Endometrial expression of these genes was evaluated using quantitative real-time RT-PCR. Results: Endometrial glycodelin mRNA expression levels (normalized to 18S rRNA expression) were increased significantly in endometrium of patients after myomectomy (P = 0.02). GPx3 mRNA expression was increased insignificantly after myomectomy (P = 0.43). Conclusion: The results showed that myomectomy increased endometrial glycodelin (significantly) and GPx3 (not significantly) gene expression after 3 months. Study at different times and detecting expression of these genes can reveal more details. Iran.